Radio afterglows of Very High Energy Gamma-ray Bursts. Issue Volume 16:Issue S363(2020) (June 2020) - Rhodes, Lauren; van der Horst, Alexander; Fender, Rob
Abstract: Five long gamma-ray bursts (GRBs) have been found to have very high energy (VHE, > 100GeV) counterparts. Interestingly, more than one emission mechanism has been invoked to explain the VHE counterpart from different events. As a result of this discovery, it has become apparent that we have been missing half of the energy produced in the afterglow of GRBs. We have been studying the radio afterglows in order to investigate whether these VHE GRBs have unusual jet properties. Studying these events in the radio waveband is advantageous as the emission at lower frequencies is brighter for longer enabling detailed, long term study of the jet evolution. The jet properties and environments of these GRBs vary hugely in a similar manner to that seen in the 'regular' long GRB population with evidence of bright reverse shock emission and multiple jet components. This work is presented on behalf of a much larger collaboration.